A LITERATURE REVIEW ON THE TEACHING OF INDONESIAN LANGUAGE IN ELEMENTARY SCHOOLS: APPROACHES, METHODS, AND PRACTICAL IMPLICATIONS - Juang Kurniawan (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to analyze the instructional approaches, methods, and contextual factors that influence the teaching of Indonesian language in elementary schools through a comprehensive literature review. Using a qualitative library research method, the study systematically reviewed academic publications from the last five years, focusing on peer-reviewed articles, empirical studies, and theoretical papers related to Indonesian language instruction. The analysis highlights the increasing adoption of student-centered methods such as contextual teaching, scaffolded literacy, and digital integration—particularly through Computer-Assisted Language Learning (CALL)—which have shown positive impacts on vocabulary development, reading comprehension, and writing fluency. However, the study also identifies significant challenges, including limited teacher training, disparities in technological infrastructure, and the linguistic diversity of students, especially in rural and multilingual school contexts. The novelty of this research lies in its integrative perspective: it does not only map teaching strategies, but also considers how instructional effectiveness is shaped by the interaction between pedagogy, digital readiness, teacher competence, and school context. Furthermore, the study provides differentiated insights that move beyond “one-size-fits-all” recommendations, offering targeted implications for various school settings. In conclusion, the findings suggest that effective Indonesian language instruction requires a flexible, context-responsive framework that aligns curriculum, method, and teacher capacity to student needs. These results are expected to inform future research, educational policy, and instructional design practices in the context of primary language education in Indonesia.